2016
DOI: 10.2217/fon-2016-0165
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Imaging Assessment of Postexternal Beam Radiation Changes of the Liver

Abstract: Radiation is being used for patients with primary and secondary liver cancers, as a rapidly evolving treatment. However, postradiation imaging changes of the liver are not well understood and therefore challenging to interpret. Distinguishing normal radiation changes from residual or recurrent disease is difficult. Size and contrast enhancement have been used to guide interpretation and clinical recommendations, but normal radiation changes can make interpretation difficult and are not accounted for in availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…The authors attributed this to the degree of tissue condensing following injection, wherein tissue volumetric integrity was better preserved and an improved representation of the tumor border was observed. Other studies have demonstrated that a large volume of liquid material leads to hardened artifacts and results in decreased imaging quality, rendering the radiotherapy unprecise (12,48). In the present study, the injection volume of 0.15 ml was not shown to reduce the CT imaging quality.…”
Section: Discussioncontrasting
confidence: 60%
“…The authors attributed this to the degree of tissue condensing following injection, wherein tissue volumetric integrity was better preserved and an improved representation of the tumor border was observed. Other studies have demonstrated that a large volume of liquid material leads to hardened artifacts and results in decreased imaging quality, rendering the radiotherapy unprecise (12,48). In the present study, the injection volume of 0.15 ml was not shown to reduce the CT imaging quality.…”
Section: Discussioncontrasting
confidence: 60%
“…Imaging features of radiation effect on hepatic parenchyma after radioembolization have not yet been well described. However, radiation-induced changes in the liver after external radiation have been reported in the previous studies ( 54 55 56 ) and can be applied in the interpretation of post-radioembolization examinations with caution. After external radiation therapy, the irradiated hepatic parenchyma frequently shows arterial hyper-enhancement on an early follow-up until 6 months which may interfere with accurate assessment of tumor response in HCC ( 54 ).…”
Section: Benign Post-treatment Imaging Findingsmentioning
confidence: 83%
“…Lack of washout appearance on the delayed phase can be helpful in differentiating radiation effect from tumor progression ( 54 ). On the portal venous phase and delayed phase images, the irradiated hepatic parenchyma can present various enhancement patterns according to the radiation dose and time interval after the treatment ( 55 ). Typical time-dependent changes are as follows: type I (within 3 months), hypo-attenuation on the portal venous phase and iso-attenuation on the delayed phase ( Fig.…”
Section: Benign Post-treatment Imaging Findingsmentioning
confidence: 99%
See 2 more Smart Citations